Ecological incumbency impedes stochastic community assembly in Holocene foraminifera from the Huon Peninsula, Papua New Guinea. Issue 4 (8th April 2011) - Reymond, Claire E.; Bode, Michael; Renema, Willem; Pandolfi, John M.
Abstract : Persistence in the structure of ecological communities can be predicted both by deterministic and by stochastic theory. Evaluating ecological patterns against the neutral theory of biodiversity provides an appropriate methodology for differentiating between these alternatives. We traced the history of benthic foraminiferal communities from the Huon Peninsula, Papua New Guinea. From the well-preserved uplifted reef terrace at Bonah River we reconstructed the benthic foraminiferal communities during a 2200-year period (9000–6800 yr B.P.) of reef building during the Holocene transgressive sea-level rise. We found that the similarity of foraminiferal communities was consistently above 60%, even when comparing communities on either side of a massive volcanic eruption that smothered the existing reef system with ash. Similarly, species diversity and rank dominance were unchanged through time. However, similarity dropped dramatically in the final stages of reef growth, when accommodation space was reduced as sea-level rise slowed. We compared the community inertia index (CII) computed from the observed species abundances with that predicted from neutral theory. Despite the differences in foraminiferal community composition in the younger part of the reef sequence, we found an overall greater degree of community inertia with less variance in observed communities than was predicted from neutral theory, regardless of foraminiferal community size or species migration rate. Thus, persistent species assemblages could not be ascribed to neutral predictions. Ecological incumbency of established foraminiferal species likely prevented stochastic increases in both migrant and rare taxa at the Bonah River site. Regardless of the structuring mechanisms, our reconstruction of Holocene foraminiferal assemblages provides historical context for the management and potential restoration of degraded species assemblages.